Low prevalence of copy number variation in pfmdr1 and pfpm2 in Plasmodium falciparum isolates from southern Angola - Denise Duarte; Francisco Manuel; Ana Dias; Esmeralda Sacato; Elsa Taleingue; Elsa Daniel; Francisco Simão; Luis Varandas; Maria Lina Antunes; Fatima Nogueira (Malaria Journal)
Abstract Background Malaria is the parasitic disease with the highest global morbidity and mortality. According to estimates from the World Health Organization (WHO), there were around 249 million cases in 2022, with 3.4% occurring in Angola. The emergence and spread of drug-resistant Plasmodium falciparum have compromised anti-malarial efficacy and threatens malaria elimination campaigns using artemisinin-based combination therapy (ACT). Increased copy number (CNV) of the P. falciparum gene plasmepsin 2 (pfpm2) have been reported to confer parasite tolerance to piperaquine (PPQ) and the multidrug resistance-1 (pfmdr1), resistance to mefloquine (MEF) and decreased susceptibility to lumefantrine (LUM). PPQ, MEF and LUM are ACT partner drugs. Therefore, CNV detection is a useful tool to track ACT resistance risk. The potential for future treatment failure of artemisinin-based combinations (that include PPQ, LUM and AMQ), due to parasite resistance in the region, emphasizes the need for continued molecular surveillance. Methods One hundred and nine clinically derived samples were collected at Hospital Central Dr. António Agostinho Neto (HCL) in Lubango, Angola. qPCR targeting the small-subunit 18S rRNA gene was used to confirm P. falciparum infection. Copy number estimates were determined using a SYBR green-based quantitative PCR assay. Results Overall, this study revealed a low number of resistance CNVs present in the parasite population at Lubango, for the genes pfmdr1 and pfpm2. Of the 102 samples successfully analysed for pfpm2 10 (9.8%) carried increased CNV and 9/101 (8.9%) carried increased CNV of pfmdr1. Conclusions This study provides, for the first time, evidence for the presence of CNVs in the pfpm2 and pfmdr1 genes in P. falciparum isolates from southern Angola.